Phosphate fertilization, biofertilizer and Bacillus sp. in peanut cultivation under salt stress - Girna dos S. Oliveira; Thales V. de A. Viana; Geocleber G. de Sousa; Samuel de O. Santos; Francisco H. R. Costa; Alisson G. da Silva; Arthur P. de A. Pereira; Fernando B. Lopes; Geovana F. Goes; Kelly N. Leite (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Peanut (Arachis hypogaea) is an important agricultural crop in Brazil, considered one of the most important oilseed crops cultivated. The use of fertilizer-solubilizing bacteria can mitigate salt stress. The objective of this study was to evaluate the gas exchange, growth, and water use efficiency of the peanut crop irrigated with brackish water under phosphate fertilization and inoculated with bacteria of the genus Bacillus sp. The experimental design used in this study was completely randomized, in a 4 × 2 × 2 factorial scheme, with 5 replicates, referring to the forms of fertilization (F1 - 0% phosphorus, F2 - 50% phosphorus, F3 - 100% phosphorus, and F4 - bovine biofertilizer), presence and absence of the inoculant and two levels of electrical conductivity of the irrigation water (ECw - 0.3 and 4.0 dS m-1). Fertilization with organic fertilizer (100% biofertilizer) and mineral fertilizer (50 and 100% phosphorus) associated with Bacillus sp. mitigated the damage caused by salt stress and promoted greater water use efficiency, chlorophyll index, internal CO2 concentration and stem diameter. The control treatment (without phosphate fertilization and without salt stress) and the application of Bacillus sp. promoted greater performance in net photosynthesis, transpiration rate, stomatal conductance, and plant height in peanut plants.